Fostering Corporate Entrepreneurship - Arthi, D; Mohan, C (Ethiopian Journal of Science and Technology, 2025)
Corporate entrepreneurship is a powerful source for change and innovation, fostering creativity and a constant search for new solutions to all kinds of problems. It can help organizations meet several challenges and can transform firms into revolutionary comparn es. It can improve corporate competitive positions as well as help overcome the lack of innovations and staleness affecting many organizations. Technological and market changes seem to occur foster than we expect, and Peter Drucker’s old saying that the only constant thing in business is change seems truer than ever. Fast-changing business environments, changing business structures and rules of competition are becoming part of the ordinary life of most companies, as these are prerequisites for staying in business. This article has been focused a commitment, competence, contribution, creati vity, confidence, innovativeness, intelligence, integrity, initativeness and insight.